Footsteps and walking trajectories during the Timed Up and Go test in young, older, and Parkinson’s disease subjects - Okada, Yohei; Yorozu, Ayanori; Fukumoto, Takahiko; Morioka, Shu; Shomoto, Koji; Aoyama, Tomoki; Takahashi, Masaki (Gait & posture, 2021)
•A laser system can easily assess footsteps and walking trajectories in TUG.•People with PD regardless of FOG turned close to the TUG marker.•Turning close to the marker in PD was related to short step length when turning.•Healthy older people turned using the large depth of space behind the marker. Footsteps and walking trajectories during the Timed Up and Go test (TUG), and their relationships with spatiotemporal gait parameters during turning in people with Parkinson’s disease (PD) and older people have not been clarified. We investigated the footsteps, walking trajectories, and spatiotemporal parameters during the TUG in PD, healthy older (HO), and healthy young (HY) subjects and the associations between the parameters of footsteps or walking trajectories and the spatiotemporal parameters during turning. Twenty-six PD, 20 HO, and 20 HY subjects participated. They performed the TUG at self-selected speed and underwent evaluations of spatiotemporal parameters in the forward, turning, and return phases and parameters of footsteps and walking trajectories by a system using laser range sensors to measure the two-dimensional distance data of the legs. Foot placement for each foot was measured as the estimated position when the leg speed of movement reached the minimum between foot-contact and foot-off. We calculated the minimum distance from a TUG marker to footsteps and the maximum anterior distance from the start to the footsteps. Step length was calculated using a method for non-linear walking. The PD subjects showed significantly smaller step lengths in all phases. The minimum distance from the marker to the footsteps in PD subjects was significantly smaller than in HO subjects and was significantly positively correlated only with the turning-phase step length. The maximum anterior distance from the start to footsteps in HO subjects was significantly larger than in PD and HY subjects and was not correlated with any spatiotemporal parameters. This study demonstrated that people with PD turn close to the TUG marker, and this turning strategy may be associated with the decreased step length when turning. These findings could help in providing instructions which prevent the exaggeration of step-length reduction when turning.